Degradasi Lignin Dan Rasio C/N Pada Proses Pengomposan Tandan Kosong Kelapa Sawit Menggunakan Trichoderma Viride Dan Mol Tapai - Helviana Dwika; Elvi Yenie; Edward Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The main constraint faced in the utilization of lignocellulosic organic waste is lignin content that is difficult to degrade both enzymatically and chemically. One solution to solve the problem is by composting method with the addition of Trichoderma viride and MOL Tapai. Composting TKKS using windrow method for 40 days. The study was conducted by varying the dosage of Trichoderma viride and MOL Tapai fungi by 50 ml Trichoderma viride, 50 ml MOL Tapai, 25 ml Trichoderma viride + 25 ml MOL Tapai, 35 ml Trichoderma viride + 15 ml MOL Tapai and 15 ml Trichoderma viride + 35 ml MOL Tapai. Measurement of lignocellulose using Chesson-Datta method. The results showed that the pH reached at the end of composting in each reactor was pH 7, the temperature during composting took place at the thermophilic condition with the highest temperature of 660C at R2, R3, and R5, 650C at R1 and R4, water content at the end of composting at each reactor is R1 35,86%, R2 37,67%, R3 37,20%, R4 35,01%, and R5 35,75%, value of C / N ratio at end of composting in each reactor ie R1 14.35, R2 13.22, R3 13.06, R4 14.20, and R5 14.35. The lowest lignocellulose value at the end of each composting was Hemiselulose 13.96% in variation R4 (TKKS + Trichoderma viride (35 ml) + MOL Tapai (15 ml)), Cellulose 14.22% in variation R4 (TKKS + Trichoderma viride (35 ml) + MOL Tapai (15 ml)), and lignin 13.56% in variation R5 (TKKS + Trichoderma viride (15 ml) + MOL Tapai (35 ml)).Keywords : lignocelluloses, Trichoderma viride, MOL Tapai